Induction of Prophage SPO2 in Bacillus subtilis by 6-(para)-Hydroxyphenylazouracil - Arwert, Fré (1974)
DNA replication in Bacillus subtilis is reversibly inhibited by 6-(para)-hydroxyphenylazouracil (HpUra) (1971), whereas replication of temperature phage SPO2 is not affected by the drug. Experiments are presented which show that HpUra will induce bacteria lysogenic for SPO2. Also, prophage φ105, which is sensitive to the drug, is induced by HpUra. Induction of SPO2 lysogenics in the presence of HpUra gives selective synthesis of SPO2 DNA.